The Effect of the Index Card Match Learning Model on the Learning Outcomes of Class V PKn - Saut Mardame Simamora; Wirda Budia Khaira (Universitas Muhammadiyah Enrekang, 2024)
This research aims to determine whether students' learning outcomes in class V in the Civics subject at SD IT Permata Medan Labuhan are influenced by the Active Learning Model of the Index Card Match Type. There are two hypotheses in this research, namely: (1) There is an influence of the Index Card Match Type Active Learning Model on student learning outcomes in class V in Civics subjects at SD IT Permata Medan Labuhan (Ha), and (2) There is no influence of the Learning Model Active Index Card Match Type on student learning outcomes in class V Civics subjects at SD IT Permata Medan Labuhan (Ho). This research uses an experimental method with a pre-experimental research type with a